Research on pulsed laser welding of TiB2-enhanced aluminum matrix composites. Issue 1 (July 2016) - Jun, Dai; Zheng, Liu; Li, Yang; Yang, Wang; Chiyu, Zhou; Yaocheng, Zhang
Abstract In this paper, pulsed laser processing technology was used to weld TiB2 -enhanced aluminum matrix composites of 2 mm thickness. The effects of welding parameters on welded joints were investigated. The results show that the effect of laser power on the weld forming is obvious. The penetration and width of welded joints were increased while the laser power was increasing. The coefficient of weld forming was changed from 4.19 to 0.997. The base metal was in full penetration when the laser power was 5.5 kW. The hardness of the fusion zone is reached 120 HV when the laser power was 6 kW. It is much higher than that of base metal because of dispersed particles TiB2 . The pulse frequency and the welding speed are very important. The good welding formation can be obtained when the parameters meet the formulafd = (3.6–5.4)v . TiB2 -enhanced aluminum matrix composites can be well welded with the pulsed laser.